Biomarkers as a tool to assess effects of chromium (VI): Comparison of responses in zebrafish early life stages and adults - Domingues, Inês
The present work aims to compare the sensitivity of embryos and adult zebrafish to chromium (VI) (as potassium dichromate) focusing on biomarkers (cholinesterase, glutathione S-transferase and lactate dehydrogenase) as endpoints. Zebrafish eggs showed less sensitivity to Cr (VI) (96 h-LC(50) = 145.7 mg/L) than adults (96 h-LC(50) = 39.4 mg/L) probably due to the protective action of the chorion. However, biomarkers were much more responsive in larvae than in adults and gave clear indications about Cr (VI) mode of action: it seems to be neurotoxic (inhibited cholinesterase), to inhibit glutathione S-transferase activity and to interfere with cellular metabolic activity (changes in lactate dehydrogenase activity) in larvae. In adults, only glutathione S-transferase was responsive, showing a clear inhibition. The responsiveness of the analyzed biomarkers in larvae reinforces the idea of the usefulness of early life stage assays in the assessment of chemicals effects. Moreover, early life stage assays also contributed with relevant information regarding anomalies in larvae development and behavior. Further research should focus on the use of biomarkers to assess long term effects which are ecologically more relevant. (C) 2010 Elsevier Inc. All rights reserved.